Development of student work sheet based on contextual approach to trigonometry material - Hermanto Hermanto; Irwan Irwan; Ridwan Ridwan (Fakultas Ilmu Pendidikan UNP)
Using Mathematics Student Worksheet (LKS) made by math teachers are not optimal, especially in helping students connect learning in life. Therefore, it is necessary to develop LKS that can provide opportunities for students to construct their knowledge, so that students can find their own learning concept. Trigonometry material is an important material in learning mathematics and relevance with other lessons. In this research, developed LKS with contextual learning approaches for trigonometric materials. The aim of this development is to produce mathematics LKS based on contextual approach which is valid, practical and effective. The subjects of the study were 29 students. Validation are done by the expert ie lecturer of mathematics education, education technology, and language. The practicality of LKS has been seen from the observation of the implementation of learning, practicality of questionnaires, interviews conducted with students and teachers. Effectiveness has been seen from the results of student learning outcomes.